Faktor yang Mempengaruhi Kejadian Stunting pada Anak Usia 24–59 Bulan di Wilayah Kerja Puskesmas Sungai Betung - Dini Fitri Damayanti; Elmina Elmina; Dianna Dianna (Malahayati Nursing Journal, 2025)
ABSTRACT Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time. The prevalence of stunting in West Kalimantan in 2021, the results of 45,892 (17.75%) children under five were stunted. Prevalence of stunting in Bengkayang Regency in 2022: 2843 (27.93%) toddlers are stunted. Analyzing Factors Related to the Incidence of Stunting in Toddlers Aged 24-59 Months in the Working Area of the Sungai Betung Health Center, Bengkayang Regency. Case Control research design. The sample in this study is divided into 2 groups as cases and controls, with the sampling technique used in this study being Random sampling, with a sample number of 88 respondents with each group of 44 cases and 44 control people. Data analysis using the chi square test. The results of the statistical test showed that there was a significant relationship between maternal nutrition in early pregnancy, history of exclusive breastfeeding, and history of anemia with stunting in children 24-59 months with a significant chi square test value with a p-value of 0.05, and there was no significant relationship between history of ANC and stunting in children aged 24-59 months (p=0.071). There was a relationship between maternal nutritional history in early pregnancy, history of exclusive breastfeeding, history of anemia during pregnancy with stunting incidence in children aged 24-59 months at Sungai Betung Health Center and no relationship between ANC history and stunting incidence in children aged 24-59 months at Sungai Betung Health Cente. Keywords: Stunting, Nutrition, Breastfeeding, Anemia, ANC  ABSTRAK Stunting merupakan sebuah masalah kurang gizi kronis yang disebabkan oleh kurangnya asupan gizi dalam waktu yang cukup lama. Prevalensi stunting di Kalimantan Barat pada tahun 2021, didapatkan hasil 45.892 (17,75%) balita mengalami stunting. Prevalensi kejadian balita stunting di Kabupaten bengkayang pada tahun 2022 2843 (27,93%) balita mengalami stunting. Menganalisis Faktor-Faktor Yang berhubungan dengan kejadian Stunting pada balita usia 24-59 bulan di wilayah kerja puskesmas Sungai Betung Kabupaten Bengkayang. Desain penelitian Case Control. Sampel dalam penelitian ini adalah dibagi menjadi 2 kelompok sebagai kasus dan kontrol,dengan teknik sampling yang digunakan dalam penelitian ini adalah Random sampling, dengan jumlah sampel yaitu 88 responden dengan masing-masing kelompok 44 orang kasus dan 44 orang kontrol. Analisa data menggunakan uji chi square. Hasil uji statistik menunjukkan bahwa terdapat hubungan yang bermakna antara gizi ibu awal kehamilan, riwayat ASI Eksklusif, dan riwayat anemia dengan stunting pada anak 24-59 bulan masing nilai uji chi square signifikan dengan p-value 0,05, dan tidak terdapat hubungan yang bermakna antara riwayat ANC dengan stunting pada anak usia 24-59 bulan (p=0,071). Ada hubungan antara riwayat gizi ibu awal kehamilan, riwayat ASI Eksklusif, riwayat anemia pada saat hamil dengan kejadian stunting pada anak usia 24-59 bulan di Puskesmas Sungai Betung dan Tidak ada hubungan antara riwayat ANC dengan kejadian stunting pada anak usia 24-59 bulan di Puskesmas Sungai Betung. Kata Kunci: Stunting, Gizi, ASI, Anemia, ANC